The role of papillary skin glands in guiding mouse pups to the nipple. Issue 2 (8th July 2020) - Klaey‐Tassone, Magali; Schaal, Benoist; Durand, Karine; Patris, Bruno; ,
Abstract: The nipple odor of lactating mice ( Mus musculus ) plays a crucial role in attracting newborn pups and motivating them to suck milk. The characteristic odor of a lactating murine nipple is assumed to be a mixture of multiple odorous substrates, that is, milk, dam's and pups' saliva, skin glands' secretions, and amniotic fluid. The present study aimed to characterize the behavioral activity of the original odor mixture that develops over the nipples in the first 2 days postpartum. We extracted this odor mixture in water and evaluated its attractive and appetitive potencies using two behavioral assays (viz., relative attraction and oral activation assays). It resulted that the so‐called nipple wash was as appetitive as fresh milk, and even more attractive than it. The behavioral potency of the nipples was shown to be specific to lactating nipples (relative to nulliparous nipples) and to be preserved for 2 weeks when stored at −80°C. Finally, we perfected a nipple deodorization procedure by inactivating the nipples' behavioral potency. We observed that such altered appetitive potency was fully restored 30 min after its washing, but without any maternal self‐licking and pups' sucking, indicating that the secretions of the nipple skin glands' were sufficient to explain the success of neonatal guidance to the nipple.